Influenza and Voter Turnout. (27th September 2016) - Urbatsch, R.
Abstract : Disease makes performing civic obligations more difficult both for the afflicted and those around them. Elections held when infectious diseases are locally prevalent are therefore likely to see lower voter turnout than are those held in healthier times. This is especially notable given the strongly seasonal incidence of influenza, which coincides with election season in some countries. This article examines the relationship between regional turnout rates in Finland and the United States from 1995 to 2015 with measures of local influenza prevalence. In both countries, regression models suggest influenza outbreaks associate with lower voting rates. This may suggest another mechanism limiting the political representation of people and communities vulnerable to ill health.